Mass Media Research - Heiner Meulemann; Jörg Hagenah (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
Mass media are defind as media which have their proper program and constitute their own audience. Mass media research, accordingly, deals with the production of programs and the consumption of the audience. For both perspectives, research topics are justified, data sources are introduced, and recommendation for the research infrastructure are given. As for media production, the establishment of a central media content archive is recommended where content analytic time series of public agencies as well as of individual researchers are collected. Furthermore, the development of a unified content analytical system and the promotion of cross-national comparisons are recommended. As for media consumption, the provision of privately funded data for the scientific community, the promotion of cross-national comparisons and the linkage of programs and audience data are recommended.
Keywords: 330; mass media; data archive; content analysis; survey research